Human ageing, longevity and evolution: can ageing be programmed? - Chmielewski, Piotr Paweł (Anthropological Review, 2019)
Understanding the proximate and ultimate causes of ageing is one of the key challenges in current biology and medicine. These problems are so important that they are sometimes referred to as the Holy Grail of biology and the Great Conundrum in biogerontology. From an evolutionary perspective, ageing is due to a failure of selection that is caused either by declining strength of selection after the onset of sexual reproduction (Medawar’s theory and Charlesworth’s model) or pleiotropic constraints (Williams’ theory). According to the disposable soma theory, which was proposed by Kirkwood and Holliday, ageing is driven by the accumulation of damage during life and failures of defensive and repair mechanisms as the more an animal expends on sexual reproduction, the less it can expend on bodily maintenance, and vice versa. Although these standard models rule out the possibility that ageing is programmed, there is no consensus about the nature of ageing within the life history in current biogerontology. Interestingly, empirical studies show that there are molecular instructions for ageing and evolutionarily conserved mechanisms for ageing, which seems inconsistent with the idea that ageing is a matter of neglect or a consequence of a failure of selection due to pleiotropic constraints. Here, selected arguments for programmed (i.e. either determined and adaptive or prearranged but non-adaptive) and non-programmed ageing are discussed. Recent advances in biogerontology that cast new light on these problems are outlined here in the context of the idea that the pace of ageing can act as an adaptation in nature, even though ageing is non-programmed and non-adaptive.